2012
DOI: 10.3329/bjar.v37i1.11189
|View full text |Cite
|
Sign up to set email alerts
|

Profitability of BARI Released Potato (Solanum tuberosum L.) Varieties in Some Selected Locations of Bangladesh

Abstract: Potato is one of the important food crops in Bangladesh. Its demand is increasing day by day. The Tuber Crop Research Centre (TCRC) of BARI released 40 HYV potato varieties and disseminated them in the farmer's fields through different agencies. But most varieties were not adopted well by the farmers due to unknown reasons. Therefore, an attempt was made to assess the level of adoption and profitability of BARI released potato variety at farm level. Data were collected from 150 randomly selected potato farmers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…1,91,345) in Munshigonj district than any other potato producing area of Bangladesh by Haque et al (2012). They also found the net return of potato cultivation was Tk.…”
Section: Profitability Of Potato Cultivationmentioning
confidence: 83%
See 4 more Smart Citations
“…1,91,345) in Munshigonj district than any other potato producing area of Bangladesh by Haque et al (2012). They also found the net return of potato cultivation was Tk.…”
Section: Profitability Of Potato Cultivationmentioning
confidence: 83%
“…The measure of the overall fit of the estimated regression, F-value (26.08) was significant at 1 percent level of significance, implying that all the explanatory variables included in the model were important for explaining the variations in gross returns of potato production. Haque et al (2012) also found all the co-efficients of human labour, land preparation, seed and NPK fertilizer were positive and significant at 1% level of significance indicating 10% increase in the cost of human labor, land preparation, seed and NPK fertilizer, remaining other factors constant would increase the yield of potato by 2.25, 0.76, 3.13 and 3.86%, respectively. Ahmed et al (2009) also carried out a research on the same and the research revealed that seed and pesticides had positive but TSP and MP had negative significant effect on gross return of potato production in Mymensing district of Bangladesh.…”
Section: Profitability Of Potato Cultivationmentioning
confidence: 90%
See 3 more Smart Citations